Development and quality evaluation of flatbread incorporated with (Colocasia esculenta) taro leaf - Balamourougane, Josephine Selvi; Shibu, Anna; Kareem, Anzil (Journal of Food Technology Research, 2025)
This study investigates the formulation of a nutritional-functional flatbread by adding taro leaf and barley powder to wheat flour. The inclusion of taro leaf and barley powder improved and increased the fiber content (1.2%), protein content (13.11%), and mineral content of dietary flatbreads, while reducing carbohydrates to 3%. For the above reasons, this product is more suitable for health-conscious consumers and plant-based diets. Dough characteristics did change slightly. The high fiber content of the ingredients led to a slight increase in hydration, with a slight reduction in extensibility. However, the dough remained workable for rolling and shaping. The structure of the flatbread held up during cooking, supporting the continued use of this nutritionally functional flatbread in semi-industrial or home preparation. Sensory evaluation indicated positive responses from consumers; in particular, the nutty flavor of barley and the earthy note of taro leaf were appreciated, with a mean score of 4.6 on a 5-point hedonic scale. Lemon juice addition improved the flavor and significantly reduced the oxalate levels in taro leaves. Microbial analysis showed that the final product was safe for consumption, with an acceptable microbial count of 2×104 CFU/g, and its shelf life, the duration during which the flatbread remains palatable, was 4 days. This nutritionally functional flatbread provides urban consumers with a nutritious, convenient, and palatable option to enhance the health aspects of their diets. The novelty of this research is based on the addition of the vastly underutilized taro leaves to a widely consumed food item, offering a solution to micronutrient insufficiency.